MEWUJUDKAN GENERASI SADAR PAJAK MELALUI PENDIDIKAN INKLUSI KESADARAN PAJAK: STUDI KASUS PADA UNIVERSITAS SELAMAT SRI - Arina Hidayati; Tri Joko Sulistiyanto; Farah Dzil Barr (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Tax Consciousness Inclusive Education is a program created by Ministry of Finance and Ministry of Research, Technology, and High Education (Indonesian: Kemenristek Dikti). Universitas Selamat Sri (UNISS) is one of universities, with 60% working students. However, the authors' preliminary observation showed only 10% of students having had Tax Identity Number (TIN or Indonesian: NPWP), and less than 10% of them having met taxpayers' obligation. The fact made the author interested in finding out